2021
DOI: 10.1039/d0ob02459g
|View full text |Cite
|
Sign up to set email alerts
|

Electrohalogenation of organic compounds

Abstract: Herein, we present an overview of recent advances in the electrochemical halogenation of organic compounds. Halogen-containing compounds are essential building blocks for post-functionalization in academic research and in different industrial...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(30 citation statements)
references
References 236 publications
0
30
0
Order By: Relevance
“…Despite a long history of bromination reactions, the search for safe and sustainable methods is continuously ongoing. [1][2][3] A large number of different methods for the synthesis of bromohydrins have been reported as these are very useful building blocks in chemistry. [4][5][6][7][8] Bromohydrins have been prepared by reacting alkenes in bromine/water 9,10 or using N-bromo succinimide (NBS)/dimethyl sulfoxide (DMSO) systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite a long history of bromination reactions, the search for safe and sustainable methods is continuously ongoing. [1][2][3] A large number of different methods for the synthesis of bromohydrins have been reported as these are very useful building blocks in chemistry. [4][5][6][7][8] Bromohydrins have been prepared by reacting alkenes in bromine/water 9,10 or using N-bromo succinimide (NBS)/dimethyl sulfoxide (DMSO) systems.…”
Section: Introductionmentioning
confidence: 99%
“…By implementing flow electrochemical methods, the scalability of processes can be facilitated while hazardous reagents such as bromine can be handled in a safe way. 3,[33][34][35] Despite the benefits of flow electrochemical methods, their use for electrochemical bromination reactions is still limited. Tan et al reported the electrophilic aromatic bromination of late-stage intermediates and drug molecules in a divided micro-flow electrochemical cell with recirculation of the substrate solution from reservoirs.…”
Section: Introductionmentioning
confidence: 99%
“…[42][43][44][45] Very recently, our group published an overview of recent advances in the electrochemical chalcogen (S/Se) functionalization of organic molecules, where more information can be found. [46] In the context of current research in electrosynthesis, based on our experience in electrosynthesis and in the chemistry of selenium compounds, [47][48][49][50][51] herein we report, for the first time, the use of an electrochemical oxidative approach to CÀ Se bond formation via the C(sp 2 )À H bond functionalization of resveratrol.…”
Section: Introductionmentioning
confidence: 99%
“…bis-selenylated product 4, the mechanism passes through product 3, followed by electrochemical oxidative C(sp 2 )À H selenylation on C-4. More information on iodination reactions via electrosynthesis can be obtained in our recently published review article, where we report on advances in the electrochemical halogenation of organic compounds [51]. In summary, we have developed an efficient procedure for the regioselective electrochemical oxidative C(sp 2 )À H selenylation of resveratrol, providing unprecedented mono-and bisselenylated compounds.…”
mentioning
confidence: 99%
“…Cognizant of the crucial role of halogens in medicine, numerous efforts have been dedicated to the development of effective halogenation reactions. 5 7 Among them, imitating environmentally benign biohalogenation has been an enduring objective for decades. Besides the proximity-guided regioselectivity to overcome the intrinsic reactivities of specific substrates in enzymatic catalysis, notably electrophilic halonium ions have been generated through leveraging their reactivity with noncovalent interactions.…”
mentioning
confidence: 99%